Distribution pattern of Algal species in Shahpura Lake, Bhopal, with respect to physicochemical parameters. - Shukla, Sangeeta (International Journal of Pharmaceutical & Biological Archive, 2017)
Shahpura Lake is situated in the posh area of Bhopal city. It is a man –made perennial lake, constructed during 1974-75.Lake water is extensively used for recreational and fishing activity. Lake is surrounded by human habitation and receives untreated domestic sewage from various points. A regular monitoring in physico-chemical parameters and distributional pattern of algal species was conducted during rainy and winter season(2016).The study reveals physico-chemicals parameters and their relation to the growth and distribution of algal population .About 29 algal species was recorded, out of which 12 algal species was found to be dominant during study period.